(3GddeY aj abg Cgd GdHjJ Ydjge GdSdGes - (3Ydj Hf GdMSjf Hf jMji Hf GdMSjf GdRjOj,J (B660 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdTaYI s
(3BNQgG (B:s
(3jfJgi HBNQ cJGH GdYJb hGdJOHjQ hGdcJGHI hGdhdGA s
(3GdLRA GdKGdK ef fSNI CNQi ai CQHYI CLRGAs
(3GdhQbI GdChdi HNW MOjKs
(3GdfSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs